2023
DOI: 10.3390/lubricants11050205
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Wear and Corrosion of Novel Electrospark and Electrospark–Electrochemical Hybrid Coatings Based on Carbon Steels

Abstract: The electrospark deposition (ESD) technique is a low-heat-input process that has great potential for coating applications and the restoration of damaged high-value parts. Carbon steels are commonly used as a substrate material for ESD coatings. However, we demonstrated that carbon steels could be used successfully as the electrode tool for the ESD process. Furthermore, ESD coatings commonly have a high as–deposited roughness. In view of this, in order to reduce the roughness of the ESD coatings, electrodeposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Based on the XRD analysis, the surface layer of samples after PENC contains mainly iron oxides Fe3O4, Fe2O3, and FeO (Figure 27a-e), which is typical for this kind of processing [3,7,10,11]. It has been shown that, with an increase in the PENC temperature, the relative amount of oxide Fe3O4 decreases, while FeO increases.…”
Section: Phase Composition Of the Nitrocarburized Surfacementioning
confidence: 88%
See 4 more Smart Citations
“…Based on the XRD analysis, the surface layer of samples after PENC contains mainly iron oxides Fe3O4, Fe2O3, and FeO (Figure 27a-e), which is typical for this kind of processing [3,7,10,11]. It has been shown that, with an increase in the PENC temperature, the relative amount of oxide Fe3O4 decreases, while FeO increases.…”
Section: Phase Composition Of the Nitrocarburized Surfacementioning
confidence: 88%
“…The tribological tests were performed according to the "shaft-block" scheme (Figure 6) [11,13]. The sample was mounted on a shaft driven by an electric motor.…”
Section: Tribological Testsmentioning
confidence: 99%
See 3 more Smart Citations